Magnetic resonance imaging (MRI) scanning for research: the experiences of healthy volunteers and patients with remitted depressive illness - Tischler, Victoria; Bronjewski, Emma; O'Connor, Katherine; Calton, Tim (Pier Professional, 2009)
We report the findings from a study exploring the experiences of individuals undergoing MRI scanning for research. Semi structured interviews took place before and after scanning with 17 participants; 12 were healthy volunteers and 5 were patients with a diagnosis of remitted depression. Themes of apprehension and curiosity prior to scanning were common in both groups. Patients were often confused about the procedure. Negative feelings were an issue at the outset, characterised by shock related to the physical surroundings, after which positive feelings, for example relaxation, were often experienced, and in the case of patients, learning more about their brain. Written information about imaging was deemed satisfactory; however the ability to ‘experience’ aspects of scanning beforehand was suggested. Scanning may be viewed as a process beginning prior to the procedure itself and involving positive and negative emotions. Increased information, reassurance and a more interactive intervention to reduce anxiety may be beneficial and may improve individuals’ experience of this widely used procedure.